2007
DOI: 10.1016/j.jinorgbio.2007.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate induces mitochondrial membrane depolarization and inhibits oxygen consumption

Abstract: Decavanadate induced rat liver mitochondrial depolarization at very low concentrations, half-depolarization with 39 nM decavanadate, while it was needed a 130-fold higher concentration of monomeric vanadate (5 lM) to induce the same effect. Decavanadate also inhibits mitochondrial repolarization induced by reduced glutathione in vitro, with an inhibition constant of 1 lM, whereas no effect was observed up to 100 lM of monomeric vanadate. The oxygen consumption by mitochondria is also inhibited by lower decavan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 43 publications
7
85
0
1
Order By: Relevance
“…17,30-53 The formation of reactive oxygen species (ROS) induced by vanadium in biological systems may involve Fenton-like reactions 48 , vanadate bioreduction mediated by reduced glutathione (GSH), flavoenzymes or nicotinamide adenine dinucleotide, reduced form (NADH), and nicotinamide adenine dinucleotide phosphate, reduced form (NADPH), oxidases 49, 50 or interaction with mitochondria. 20, 30 Mitochondria, a potential producer of ROS, have recently been suggested as a potential target of vanadium, decavanadate or monomeric vanadate, since mitochondrial membrane depolarization is a key event in vanadate-induced necrotic cell death of cardiomyocytes. 20 Moreover, efforts have been dedicated in recent years to learn more about the characterization of effects in bone-derived systems by vanadium, namely signalling pathways, extracellular matrix inhibition and inhibition of alakaline phosphatase activity, that impact cell differentiation.…”
Section: The Role Of Vanadium Versus Pharmacological and Medicinal Efmentioning
confidence: 99%
“…17,30-53 The formation of reactive oxygen species (ROS) induced by vanadium in biological systems may involve Fenton-like reactions 48 , vanadate bioreduction mediated by reduced glutathione (GSH), flavoenzymes or nicotinamide adenine dinucleotide, reduced form (NADH), and nicotinamide adenine dinucleotide phosphate, reduced form (NADPH), oxidases 49, 50 or interaction with mitochondria. 20, 30 Mitochondria, a potential producer of ROS, have recently been suggested as a potential target of vanadium, decavanadate or monomeric vanadate, since mitochondrial membrane depolarization is a key event in vanadate-induced necrotic cell death of cardiomyocytes. 20 Moreover, efforts have been dedicated in recent years to learn more about the characterization of effects in bone-derived systems by vanadium, namely signalling pathways, extracellular matrix inhibition and inhibition of alakaline phosphatase activity, that impact cell differentiation.…”
Section: The Role Of Vanadium Versus Pharmacological and Medicinal Efmentioning
confidence: 99%
“…On the other hand, V 5+ reacted with thiols to produce V 4+ and thiyl radicals [7]. Several studies have associated V 5+ -toxicity with its capacity to induce the formation of reactive oxygen species (ROS), probably by interacting with mitochondrial redox centers [8][9][10]. It is generally known that the GSH-related thiols participate in many important biological reactions, including the protection of cell membranes against oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that decavanadate is stronger than vanadate in inducing membrane depolarization and inhibiting oxygen consumption to isolated hepatic and cardiac mitochondria (Soares et al 2007a). …”
Section: Redox Properties Of Decavanadatementioning
confidence: 99%